Responsibilities, Rights, and Independence of Shariah Committees in Islamic Financial Institutions based on Shariah Governance 2019 - Mohd Noor, Noor Fadhzana; Ismail, Noor Affendi (Selangor Humaniora Review, 2021)
Shariah governance forms an essential part of corporate governance within an Islamic bank. The objective of Shariah Governance is to ‘ensure Shariah compliance’ and to ‘strengthen public confidence in the integrity, management and business operations of the Islamic financial institutions’. Among the key function within Shariah governance is the Shariah committee. However, past studies have shown that there are issues related to the independence of the Shariah committee that may affect it in discharging its responsibilities. The independence is vital because the Shariah committee is accountable towards God as well as the shareholders. Thus, the objective of this study is to examine the independence of the Shariah committee within the aspects of significance, roles, rights, and responsibilities of the committee based on Shariah Governance 2019 in comparison to Shariah Governance Framework 2010. This study employs summative content analysis and comparative analysis on relevant legislation and past literature on Shariah committees in Malaysia. It was found that the significance, roles, rights, and responsibilities of the Shariah committees in Malaysia have been duly established within the Malaysian legal framework. Some enhancements are evident in the current Shariah Governance 2019 compared to the Shariah Governance Framework 2010. However, the enhancements also have reconceptualized the independence of the SC of the IFIs. On the bright side, it may be the original intention of BNM, perhaps to ensure standardization and reduce legal risks within the practice of Shariah compliance. On the other side, it is not clear how the SG 2019 has and will mould the decision-making minds of the SC members within IFIs.